Method for improving dispersity of carbon nano composite material

Through oxygen plasma modification treatment and the addition of sodium bicarbonate and nanocalcium carbonate to the carbon nanocomposite materials, combined with mechanical stirring and ultrasonic treatment, the problem of insufficient dispersion of carbon nanocomposite materials is solved, and a more uniform and stable dispersion effect is achieved.

CN119841307APending Publication Date: 2025-04-18QIEN INTELLIGENT TECHNOLOGY (TIANJIN) CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510329105.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the dispersion of carbon nanocomposites in the matrix, resulting in uneven dispersion and poor product consistency and stability.

Method used

By undergoing oxygen plasma modification on the carbon nanomaterial, functional groups are grafted, and sodium bicarbonate and nanocalcium carbonate are added to the aqueous solution, combined with mechanical stirring and ultrasonic treatment, the dispersion of carbon nanomaterials is gradually improved.

Benefits of technology

It significantly improves the dispersion of carbon nanocomposites, avoids agglomeration, and improves the consistency and stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841307A_ABST
    Figure CN119841307A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the dispersity of a carbon nano composite material. The method comprises the following steps: carrying out plasma modification treatment on a carbon nano material; uniformly dividing the carbon nanomaterial into four parts; adding sodium bicarbonate into deionized water to obtain a solution A; adding one part of the carbon nanomaterial and a dispersing agent with the same mass into the solution A to obtain a solution B; carrying out mechanical stirring and ultrasonic treatment on the solution B; repeating for three times to obtain a carbon nanomaterial pre-dispersion liquid; mixing the carbon nanomaterial pre-dispersion liquid and nano calcium carbonate, and adding the mixture into the precursor solution of the matrix to obtain a solution C; mechanically stirring the solution C to obtain a solution D; and carrying out centrifugal defoaming on the solution D, and finally, uniformly dispersing the carbon nanomaterial in the precursor solution of the matrix. According to the invention, nano calcium carbonate is added, so that the distance between carbon nanoparticles is increased, and agglomeration is avoided; sodium bicarbonate is added, and the dispersion effect can be improved in an alkaline environment; and uniformly distributing the carbon nanomaterial, sequentially adding and carrying out ultrasonic treatment to improve the dispersion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of carbon nanocomposite materials, and in particular to a method for improving the dispersibility of carbon nanocomposite materials. Background Art

[0002] The high conductivity and excellent mechanical properties of carbon nanocomposites make them ideal conductive electronic materials and are widely used in electronic devices such as field effect transistors and strain sensors. Carbon nanocomposites are usually composed of conductive fillers (carbon nanotubes, graphene, carbon black, etc.) and non-conductive matrix (resin, biodegradable plastic Ecoflex, polydimethylsiloxane, etc.). The role of the conductive filler is to form a conductive path in the non-conductive matrix, giving the composite material conductive properties. The role of the matrix is ​​to give the composite material flexibility and stretchability.

[0003] The dispersibility of carbon nanomaterials refers to their dispersion degree and stability in the medium, which is one of the key factors affecting the application effect of carbon nanomaterials. Due to the surface inertness and strong van der Waals forces between carbon nanomaterials, the problem of uneven dispersion of conductive fillers in the matrix will occur when preparing carbon nanocomposites, which seriously affects the consistency and stability of carbon nanocomposite products.

[0004] In the prior art, carbon nanocomposites are prepared by mechanical stirring and ultrasonic dispersion. Mechanical stirring uses mechanical energy such as shear force or impact force generated by external force to disperse nanoparticles in the medium. However, for strongly agglomerated materials such as carbon nanotubes, the shear force generated by mechanical stirring may not be sufficient to completely break its agglomeration structure. Ultrasonic dispersion uses high-frequency vibrating ultrasound to disperse materials into tiny particles. Although the cavitation effect of ultrasound can produce a local high-temperature and high-pressure environment and microjets with strong impact force, which are conducive to the formation of tiny particles and the shearing effect on agglomerates, this effect may not be thorough enough for tightly entangled carbon nanotubes. Therefore, it is necessary to change the chemical properties of the surface of carbon nanomaterials, reduce their surface energy, and thus improve their dispersibility in the medium. Summary of the invention

[0005] The present invention aims to solve the deficiencies of the prior art and provide a method for improving the dispersibility of carbon nanocomposite materials.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for improving the dispersibility of carbon nanocomposite materials, comprising the following steps:

[0008] S1, performing plasma modification treatment on the carbon nanomaterial for 3 minutes to graft new functional groups thereon;

[0009] S2, 0.2g of carbon nanomaterial is evenly divided into four parts;

[0010] S3, adding 0.05 g of sodium bicarbonate to 50 ml of deionized water to obtain solution A;

[0011] S4, adding one portion of the carbon nanomaterial in step S2 and an equal mass of a dispersant to solution A to obtain solution B;

[0012] S5, mechanically stirring solution B, maintaining the temperature at 20°C-30°C, maintaining the mechanical stirring speed at 800-1000 rpm, and stirring for 45 minutes;

[0013] S6, the mechanically stirred solution B was further subjected to ultrasonic treatment, the temperature was maintained at 10°C, the ultrasonic power was 1200 W, the ultrasonic on time was 1 second, the ultrasonic off time was 2 seconds, and the total ultrasonic treatment time was 1 hour;

[0014] S7, repeating steps S4-S6 three more times to obtain a carbon nanomaterial pre-dispersion liquid;

[0015] S8, mixing the carbon nanomaterial pre-dispersion liquid and 0.03 g of nano calcium carbonate and adding the mixture to the precursor solution of the matrix to obtain a solution C;

[0016] S9, continue to mechanically stir solution C, maintain the mechanical stirring speed at 800-1000 rpm, and stir for 1 hour to obtain solution D;

[0017] S10, centrifugally degas the solution D for 5 minutes, and finally the carbon nanomaterials are evenly dispersed in the precursor solution of the matrix.

[0018] In step S1, the carbon nanomaterial is any one of carbon nanotubes, graphene, and carbon black.

[0019] In step S1, the gas used in the plasma modification process is oxygen.

[0020] The dispersant in step S4 is sodium dodecylbenzene sulfonate or polyvinyl pyrrolidone.

[0021] The precursor solution of the substrate in step S4 is one of resin, Ecoflex and polydimethylsiloxane.

[0022] The beneficial effects of the present invention are as follows: the present invention firstly utilizes oxygen plasma to treat the carbon nanomaterials. During the plasma treatment process, these high-energy particles can interact with the surface of the carbon nanomaterials and graft new functional groups (such as hydroxyl groups, carboxyl groups, etc.); at the same time, nano calcium carbonate is added to increase the distance between the carbon nanoparticles, which can effectively prevent the carbon nanomaterials from agglomerating; sodium bicarbonate is added to make the aqueous solution weakly alkaline, and the alkaline environment can improve the dispersion effect of the carbon nanomaterials; the carbon nanomaterials are evenly divided and added in sequence and ultrasonically treated, which avoids the reduction of the dispersion effect due to high concentration. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flow chart of the specific operation steps of the present invention;

[0024] Figure 2 This is a schematic diagram of the carbon nanomaterial pre-dispersion liquid obtained in Comparative Example 1 of the present invention after being left to stand for 7 days;

[0025] Figure 3 This is a schematic diagram of the carbon nanomaterial pre-dispersion liquid obtained in the specific embodiment 1 of the present invention after being left to stand for 7 days;

[0026] Figure 4 This is a SEM image of the carbon nanomaterial mixed with the matrix in Comparative Example 1 of the present invention;

[0027] Figure 5 This is a SEM image of the carbon nanomaterial mixed with the matrix in the specific embodiment 1 of the present invention;

[0028] The following is a detailed description of the embodiments of the present invention with reference to the accompanying drawings. DETAILED DESCRIPTION

[0029] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention. The present invention is described in more detail by way of example with reference to the accompanying drawings in the following paragraphs. The advantages and features of the present invention will become clearer according to the following description. It should be noted that the accompanying drawings are all in a very simplified form and are not in precise proportions, and are only used to facilitate and clearly assist in explaining the purpose of the embodiments of the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0031] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Specific embodiment 1:

[0033] A method for improving the dispersibility of carbon nanocomposites, such as Figure 1 As shown, the specific steps are:

[0034] S1, performing plasma modification treatment on the carbon nanomaterial for 3 minutes to graft new functional groups thereon; the carbon nanomaterial is any one of carbon nanotubes, graphene, and carbon black; the gas used in the plasma modification treatment is oxygen;

[0035] S2, 0.2g of carbon nanomaterial is evenly divided into four parts;

[0036] S3, adding 0.05 g of sodium bicarbonate to 50 ml of deionized water to obtain solution A;

[0037] S4, adding one portion of the carbon nanomaterial in step S2 and an equal mass of a dispersant to solution A to obtain solution B; the dispersant is sodium dodecylbenzene sulfonate or polyvinyl pyrrolidone;

[0038] S5, mechanically stirring solution B, maintaining the temperature at 20°C-30°C, maintaining the mechanical stirring speed at 800-1000 rpm, and stirring for 45 minutes;

[0039] S6, the mechanically stirred solution B was further subjected to ultrasonic treatment, the temperature was maintained at 10°C, the ultrasonic power was 1200 W, the ultrasonic on time was 1 second, the ultrasonic off time was 2 seconds, and the total ultrasonic treatment time was 1 hour;

[0040] S7, repeating steps S4-S6 three more times to obtain a carbon nanomaterial pre-dispersion liquid;

[0041] S8, mixing the carbon nanomaterial pre-dispersion liquid and 0.03 g of nano calcium carbonate and adding the mixture to the precursor solution of the matrix to obtain solution C; the precursor solution of the matrix is ​​one of resin, Ecoflex, and polydimethylsiloxane;

[0042] S9, continue to mechanically stir solution C, maintain the mechanical stirring speed at 800-1000 rpm, and stir for 1 hour to obtain solution D;

[0043] S10, centrifugally degas the solution D for 5 minutes, and finally the carbon nanomaterials are evenly dispersed in the precursor solution of the matrix.

[0044] The above method is used to improve the dispersibility of carbon nanocomposites. The principle is:

[0045] First, the original carbon nanomaterial is modified by oxygen plasma treatment, so that the carbon nanomaterial is grafted with functional groups such as carboxyl and hydroxyl groups to produce binding sites that are easy to react chemically. After the carbon nanomaterial treated with oxygen plasma is divided, one portion and 0.05g sodium bicarbonate and a dispersant of equal mass are added to deionized water, and then mechanical stirring is performed, followed by ultrasonic treatment, and then the next portion of carbon nanomaterial is added to the solution, mechanical stirring and ultrasonic treatment are performed, and the steps are repeated until all carbon nanomaterials are processed. After the carbon nanomaterial is divided, the pre-dispersion treatment is performed step by step, which can fully ensure the dispersion effect. Sodium bicarbonate can make the aqueous solution weakly alkaline, and the alkaline environment can improve the dispersion effect of the carbon nanomaterial. The treated carbon nanomaterial and 0.03g nano calcium carbonate are further mixed with the precursor solution of the matrix, and mechanical stirring is performed first to make the carbon nanomaterial preliminarily dispersed in the matrix. The role of nano calcium carbonate is to separate the carbon nanomaterial and avoid agglomeration of the carbon nanomaterial. The treated mixed solution is mechanically stirred again to accelerate the dispersion of the carbon nanomaterial in the matrix precursor solution, and finally the bubbles in the mixed solution are removed by centrifugal degassing technology to obtain a carbon nanocomposite material with higher dispersion.

[0046] Comparative Example 1:

[0047] A method for preparing a carbon nanocomposite material, comprising the following specific steps:

[0048] P1, mixing the carbon nanomaterial and the dispersant in a mass ratio of 1:1 and adding the mixture into the precursor solution of the matrix;

[0049] P2. Mechanically stir the solution obtained in the previous step, keep the temperature at 20°C-30°C, keep the mechanical stirring speed at 800-1000 rpm, and stir for 3 hours;

[0050] P3, continue to ultrasonically treat the mechanically stirred solution, keep the temperature at 10°C, the ultrasonic power at 1200W, the ultrasonic on time at 1 second, the ultrasonic off time at 2 seconds, and the total ultrasonic treatment time at 4 hours to obtain a carbon nanomaterial pre-dispersion solution;

[0051] P4. The obtained solution is subjected to centrifugal degassing for 5 minutes, and finally the carbon nanomaterial is dispersed in the precursor solution of the matrix.

[0052] The carbon nanomaterial pre-dispersion liquid obtained in Comparative Example 1 was left to stand for 7 days. Figure 2 As shown, the carbon nanomaterial pre-dispersion liquid obtained in specific embodiment 1 was left to stand for 7 days. Figure 3 As shown, it can be observed that the carbon nanomaterial pre-dispersion liquid in Comparative Example 1 has obvious precipitation, while the carbon nanomaterial pre-dispersion liquid in Specific Example 1 does not have obvious precipitation, and the dispersion effect is better.

[0053] The SEM image of the carbon nanomaterial mixed with the matrix in Comparative Example 1 is as follows: Figure 4 As shown, the SEM image of the carbon nanomaterial mixed with the matrix in the specific embodiment 1 is as follows Figure 5 As shown, it can be observed that the carbon nanocomposite material in Comparative Example 1 is not uniformly dispersed, while the carbon nanocomposite material in Specific Example 1 is relatively uniformly dispersed.

[0054] The present invention firstly utilizes oxygen plasma to treat the carbon nanomaterial. During the plasma treatment process, these high-energy particles can interact with the surface of the carbon nanomaterial and graft new functional groups (such as hydroxyl, carboxyl, etc.); at the same time, nano calcium carbonate is added to increase the distance between the carbon nanoparticles, which can effectively prevent the carbon nanomaterial from agglomerating; sodium bicarbonate is added to make the aqueous solution weakly alkaline, and the alkaline environment can improve the dispersion effect of the carbon nanomaterial; the carbon nanomaterial is evenly divided and added in sequence and ultrasonicated, which avoids the reduction of the dispersion effect due to high concentration.

[0055] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A method for improving the dispersibility of carbon nanocomposite materials, characterized in that: The specific steps are: S1, performing plasma modification treatment on the carbon nanomaterial for 3 minutes to graft new functional groups thereon; S2, 0.2g of carbon nanomaterial is evenly divided into four parts; S3, adding 0.05 g of sodium bicarbonate to 50 ml of deionized water to obtain solution A; S4, adding one portion of the carbon nanomaterial in step S2 and an equal mass of a dispersant to solution A to obtain solution B; S5, mechanically stirring solution B, maintaining the temperature at 20°C-30°C, maintaining the mechanical stirring speed at 800-1000 rpm, and stirring for 45 minutes; S6, the mechanically stirred solution B was further subjected to ultrasonic treatment, the temperature was maintained at 10°C, the ultrasonic power was 1200 W, the ultrasonic on time was 1 second, the ultrasonic off time was 2 seconds, and the total ultrasonic treatment time was 1 hour; S7, repeating steps S4-S6 three more times to obtain a carbon nanomaterial pre-dispersion liquid; S8, mixing the carbon nanomaterial pre-dispersion liquid and 0.03 g of nano calcium carbonate and adding the mixture to the precursor solution of the matrix to obtain a solution C; S9, continue to mechanically stir solution C, maintain the mechanical stirring speed at 800-1000 rpm, and stir for 1 hour to obtain solution D; S10, centrifugally degas the solution D for 5 minutes, and finally the carbon nanomaterials are evenly dispersed in the precursor solution of the matrix.

2. A method for improving the dispersibility of carbon nanocomposite materials according to claim 1, characterized in that: In step S1, the carbon nanomaterial is any one of carbon nanotubes, graphene, and carbon black.

3. A method for improving the dispersibility of carbon nanocomposite materials according to claim 2, characterized in that: In step S1, the gas used in the plasma modification process is oxygen.

4. A method for improving the dispersibility of carbon nanocomposite materials according to claim 3, characterized in that: The dispersant in step S4 is sodium dodecylbenzene sulfonate or polyvinyl pyrrolidone.

5. A method for improving the dispersibility of carbon nanocomposite materials according to claim 4, characterized in that: The precursor solution of the substrate in step S4 is one of resin, Ecoflex and polydimethylsiloxane.

Citation Information

Patent Citations

  • Method of dispersing carbon nano-tube with nano particle permeation technique

    CN101108315A

  • Compound dispersing agent of carbon nanomaterial and method for preparing electric conduction polymeric composite thereof

    CN103333368A

  • Graphene dispersion liquid and preparation method thereof

    CN107445155A

  • Device and method for improving dispersibility of atmospheric pressure pulse discharge plasma modified nanoparticles in matrix material

    CN111741581A

  • Nano modified composite material and preparation method and application thereof

    CN113248868A